2011
DOI: 10.1007/s00436-011-2302-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an energy block containing Duddingtonia flagrans in the control of gastrointestinal nematodes of sheep

Abstract: The efficacy of the nematode-trapping fungus Duddingtonia flagrans incorporated into an energy block was evaluated for the control of gastrointestinal nematodes in sheep. Four naturally parasitised sheep with average nematode egg counts of 2,470 eggs per gram grazed by pairs on two similar parasite-free paddocks for 30 days. During that period, one pair of sheep (treated animals, T1) received an energy block containing chlamydospores of D. flagrans at a dose of 200,000 chlamydopores/kg bw/day, while the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Although different fungus MICs were observed, D. flagrans showed the lowest MICs against all drugs tested. As this is one of the most effective predatory fungi against endoparasites (Braga et al, 2011;Sagüés et al, 2011), the results of this study demonstrate the importance of compatibility tests between anthelmintics and nematophagous fungi. On the other hand, the MICs obtained against ivermectin, employed both as an anthelmintic and in ruminant tick control, suggest that the compatibility of this chemical with other biological practices must be known so as to avoid loss of control efficiency.…”
Section: Discussionsupporting
confidence: 56%
“…Although different fungus MICs were observed, D. flagrans showed the lowest MICs against all drugs tested. As this is one of the most effective predatory fungi against endoparasites (Braga et al, 2011;Sagüés et al, 2011), the results of this study demonstrate the importance of compatibility tests between anthelmintics and nematophagous fungi. On the other hand, the MICs obtained against ivermectin, employed both as an anthelmintic and in ruminant tick control, suggest that the compatibility of this chemical with other biological practices must be known so as to avoid loss of control efficiency.…”
Section: Discussionsupporting
confidence: 56%
“…Prior studies in laboratory, as well as in open field conditions, have shown that nematophagous fungi are capable of controlling infectious forms (L 3 ) of a wide variety of gastrointestinal parasites in domestic animals with success, with special distinction to the species Duddingtonia flagrans (Sagüés et al 2011;Santurio et al 2011). However, for a fungus species to be considered as effective in controlling a range of specified parasites, it is important for it to conserve its predative properties after a complete gastrointestinal transit, besides successfully capturing the aforementioned prey (Waller et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…This issue has encouraged the search for novel methods including the 67 biological control by the use of nematophagous fungi against the free living stages of 68 the parasite on pasture (Waller, 1997;Waller et al, 2001a). Biological control offers an 69 effective, renewable and environmentally sound alternative in the reduction of infective 70 larva populations of nematodes in pastures (Larsen, 1999) blocks (Sagüés et al, 2011). The success of all the above mentioned alternatives was 78 found to be dependent on the voluntary and variable intake of the animals which lead to 79 unpredictable results (Waller, 1997;Waller et al, 2001b).…”
mentioning
confidence: 99%